2018
DOI: 10.6060/tcct.20165903.5313
|View full text |Cite
|
Sign up to set email alerts
|

Ozonolytic Transformations of (R)-4-Menthene-3-One and Its Derivatives in Direction to Low Molecular Weight Bioregulators

Abstract: The author’s data on ozonolytic decyclization (ring opening) of (R)-4- menthene-3-one and its alkylated analogues and application of non-peroxide ozonolysis products in the synthesis of optically active low molecular weight bioregulators including the insects pheromones and juvenoids were generalized. The results of comparative reactivity of the mentioned above mono-terpenoid in the set of α, β-unsaturated cyclic enones were represented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The features of the conformational structure are confirmed by the nuclear magnetic resonance (NMR) spectra H 1 and C 13, 15,51 according to which the inversion of the cycle in the (R)‐4‐menthen‐3‐one is difficult because the signals of conformers 1b and 1d are absent in the spectra 52 …”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The features of the conformational structure are confirmed by the nuclear magnetic resonance (NMR) spectra H 1 and C 13, 15,51 according to which the inversion of the cycle in the (R)‐4‐menthen‐3‐one is difficult because the signals of conformers 1b and 1d are absent in the spectra 52 …”
Section: Resultsmentioning
confidence: 98%
“…Due to the peculiarities of the structure of pheromones in developing convenient ways of their synthesis, the starting compound is of great importance, which should be polyfunctional and contain an optically active center remote from the reaction groups. It has been shown that monoterpenoids such as (R)‐4‐menthen‐3‐one ( 1 ), 4 R‐(−)‐сarvone ( 2 ) 5 and (R)‐(+)‐pulegone ( 3 ) 6 (Figure 1) meet the specified criteria and were successfully used for the synthesis of a wide variety of pheromones 7–13 . Of all the monoterpenoids used, it is (R)‐4‐menthen‐3‐one ( 1 ) that has the most convenient structure for subsequent transformations and can be easily obtained on the basis of l‐menthol 4 extracted from mint oil 14…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations